PERANCANGAN DAN IMPLEMENTASI SISTEM ANJUNGAN PENDAFTARAN MANDIRI DI RUMAH SAKIT PARU DR. ARIO WIRAWAN SALATIGA MENGGUNAKAN ALGORITMA FIFO. - Fendy Tri Anggoro; Fatkhul Amin (Elkom : Jurnal Elektronika dan Komputer, 2023)
Pulmonary Hospital dr. Ario Wirawan Salatiga is a health service institution that organizes plenary health. In the era of the Covid-19 pandemic, dr. Ario Wirawan experienced a significant increase so that during administration the patient experienced a long waiting time. The preparation of this research aims to develop an independent registration system so that it can manage long and ineffective queues. This self-registration platform system uses a web-based FIFO (First in First Out) algorithm. The system development stage is the analysis, design, design and testing stage. The method for developing an independent registration platform system uses the prototype method according to needs. While the coding stage of this system was built using the Python programming language with the PostgreSQL database. With the existence of an independent registration platform system, it is hoped that the hospital and patients can be facilitated in the examination registration process and managing patient data at the Pulmonary Hospital dr. Ario Wirawan Salatiga.  Keywords: FIFO, Automated Pavement System